Implementation Of Aristotic Character Education In Elementary School Learning Constructivism - Cahyadi, Fajar; Muttaqin, Muhammad Fauzan (International Journal of Research in Education, 2025)
The purpose of the study is to analyze the theoretical implementation between character education based on Aristotle's understanding and learning constructivism in the context of basic education. The research method uses qualitative descriptive analysis. The location of the research is SD Negeri 5 Cipondoh Makmur. Data collection uses observations, interviews, and documentation studies. Data collection was carried out for 2 sessions and validated using data triangulation and source triangulation. Data analysis uses interactive analysis through reduction, data display and inference. The results of the study show that character education based on Aristotle's understanding offers a rich and relevant approach in shaping children's character in elementary school. Through habituation of good behavior and hands-on experience, Aristotle's principles can be integrated into classroom learning to help children develop positive habits. In addition, this approach can be integrated with the principles of learning constructivism, which emphasizes the active role of learners in building their own knowledge through hands-on experience and reflection. The implication is to shape the character of children in elementary school through creating a learning environment that supports character formation, paying attention to the role of parents and the social environment.